2023
DOI: 10.1161/jaha.123.030220
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight Is Associated With Clonal Hematopoiesis of Indeterminate Potential and Cardiovascular Outcomes in Adulthood

Abstract: Background High and low birth weight are independently associated with increased cardiovascular disease risk in adulthood. Clonal hematopoiesis of indeterminate potential (CHIP), the age‐related clonal expansion of hematopoietic cells with preleukemic somatic mutations, predicts incident cardiovascular disease independent of traditional cardiovascular risk factors. Whether birth weight predicts development of CHIP later in life is unknown. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…By reconstructing hematopoietic phylogenies using whole-genome sequencing of 12 MPN patients, one study reported DNMT3A and JAK2 V617F mutations arising as early as 8 and 33 weeks of gestation, respectively ( 33 ). Moreover, a retrospective cohort study of the UK Biobank reported an association between abnormal birth weight, both low and high, and CHIP incidence, with a particular association (OR, 1.04 per 1 kg increase) between DNMT3A CHIP and higher birth weight ( 34 ). Although these studies showcase great strides in improved detection of rare mutant HSPC clones that allow us to infer potential origins for CHIP-associated mutations, more work is required to precisely identify when CHIP mutations, and the processes that select for them, occur in an individual’s life.…”
Section: Chip and Hematopoietic Development: Where Does The Journey B...mentioning
confidence: 99%
“…By reconstructing hematopoietic phylogenies using whole-genome sequencing of 12 MPN patients, one study reported DNMT3A and JAK2 V617F mutations arising as early as 8 and 33 weeks of gestation, respectively ( 33 ). Moreover, a retrospective cohort study of the UK Biobank reported an association between abnormal birth weight, both low and high, and CHIP incidence, with a particular association (OR, 1.04 per 1 kg increase) between DNMT3A CHIP and higher birth weight ( 34 ). Although these studies showcase great strides in improved detection of rare mutant HSPC clones that allow us to infer potential origins for CHIP-associated mutations, more work is required to precisely identify when CHIP mutations, and the processes that select for them, occur in an individual’s life.…”
Section: Chip and Hematopoietic Development: Where Does The Journey B...mentioning
confidence: 99%